Respuesta :
Answer:
Step-by-step explanation: All we are doing here is inserting 2 in place of all the x variables. So that is written as 12(2)-3(3(2)-5)+24. Next, we follow the order of operations to solve
1) Multiply 3 by 2 and subtract by 5 inside the parenthesis = 12(2)-3-1+24
2) Multiply 12 by = 24-3+1+24
3) subtract 3 from 24 = 21+24
4) Add the final two terms = 45
MARK BRAINLIEST
(12)(2)-3((3)(2)-5)+24
=24-3((3)(2)-5)+24
=24-3(6-5)+24
=24-(3)(1)+24
=24-3+24
=21+24
=45
Sorry the parentheses got to be a lot LMMMMAAAAOOO anyways please mark as brainliest
=24-3((3)(2)-5)+24
=24-3(6-5)+24
=24-(3)(1)+24
=24-3+24
=21+24
=45
Sorry the parentheses got to be a lot LMMMMAAAAOOO anyways please mark as brainliest